Contribuciones temporales para el impulso económico post covid 19 y su incidencia en las utilidades de las cooperativas de ahorro y crédito del segmento 1 de la provincia de Pichincha durante el periodo 2021-2022. - Álvarez Espín, Angie Nicole (2023)
After the COVID-19 pandemic, government revenues are lower than expenses, resulting in a fiscal deficit, which is presented by: low tax collection as a result of the closure of commercial activities, increased public spending, and a high public debt due to international credits for the State; implying that they generate an interestwhich is a negative aspect that reduces the ability to finance social needs. For this reason, the Economic Impulse Law was created, which focuses on temporary contributions, for companies that own equal or more than 5,000,000 dollars as of December 31, 2020, the risk is evident in the popular and solidarity sector, because they must contribute with this which is not considered for tax credit or deductible for the payment. For these reasons, the objective of this Research Project is to analyze the Temporary Contributions of the Post COVID-19 Economic Boost and its impact on the profits of the Savings and Credit Cooperatives of Segment 1 of the Province of Pichincha during the 2021 period. -2022. According to the results obtained, the COACs of segment 1 of Pichincha, jointly, for 2020 reached a patrimony of $482,035,667.35, and after the validity and application of the law that regulates temporary contributions for 2022, these Companies contributed $3,856,285.34, representing 2.30% of the total corporate collection of Pichincha and a drop in the profits of four of the seven COAC, such as Alianza del Valle, Cooprogreso, De los Servidores Públicos del Ministerio de Educación y Cultura y Policía Nacional Limitadas, placing the solvency and reinvestments of said institutions at risk.